(untitled) (New York, 2014)
Fundamentals of Human Communication presents the basic theoretical and practical concepts of the human communication process. DeFleur uses a multidisciplinary approach, with a balance of innovative and traditional perspectives to give students the tools to communicate effectively in the workplace and in everyday situations.
Keywords: Communication,Giao tiếp